1996
DOI: 10.1007/bf00497805
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline attenuates ischemia/reperfusion injury to the small intestine in the rat

Abstract: There is a large body of evidence that neutrophils may play an important role in the mucosal injury that follows ischemia of the intestine. Pentoxifylline (PTF), a methylxanthine derivative, prevents leukocyte adherence to vascular endothelium and restores intestinal blood flow following hemorrhagic shock and sepsis. The purpose of this study was to evaluate the protective properties of PTF in an ischemia-reperfusion model of the intestine and whether its action is mediated through tissue neutrophils as assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…[44][45][46] This is the first study of a small intestinal ischemia used for survival of more than a few hours when evaluating the clinical response of ischemic injured small bowels. [27][28][29][30][31][32] In fact, survival in this study was extended to 7 days to demonstrate the complete effect of PTX pharmacological treatment on this important clinical endpoint. Only 1 other work by Tireli and associates 4 used 7-day testing, but in a different context, where PTX was used to observe its effect on healing of ischemic small intestine anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[44][45][46] This is the first study of a small intestinal ischemia used for survival of more than a few hours when evaluating the clinical response of ischemic injured small bowels. [27][28][29][30][31][32] In fact, survival in this study was extended to 7 days to demonstrate the complete effect of PTX pharmacological treatment on this important clinical endpoint. Only 1 other work by Tireli and associates 4 used 7-day testing, but in a different context, where PTX was used to observe its effect on healing of ischemic small intestine anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32] A search of the literature using the wording "pentoxifylline in intestinal ischemia" returned only 25 articles between1992 and the date of this study, of which, only 5 studies were similar to our current work. [28][29][30][31][32] However, when we searched more general wording "pentoxifylline in ischemia," we found 307 articles. This led us to believe that the interest in using PTX has not been in small intestinal ischemia but rather, on other types of ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 15 , 18 22 Few studies reported in the literature have addressed the role of PTX in small intestinal I/R. 7 , 15 , 18 – 23 The present study on the mechanisms underlying the protective effect of PTF in small intestinal ischemia specifically suggests that the anti-inflammatory action of PTF is very important. This study indicates that PTX reduces the levels of TNFα, IL-1β, and IL-6 after severe organ ischemia in rats, which may have important implications for ischemia outcomes because these three proinflammatory cytokines are regulators of the inflammatory response in human and animal ischemic cells.…”
Section: Discussionmentioning
confidence: 75%
“…Our findings are similar to those of other studies that investigated the effects of PTF on ischemic small bowel injury. 7 , 15 , 18 22 …”
Section: Discussionmentioning
confidence: 99%